2000
DOI: 10.1021/es991325m
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and Accumulation of Gold(III) by Medicago sativa Alfalfa Biomass:  X-ray Absorption Spectroscopy, pH, and Temperature Dependence

Abstract: We report herein the use of alfalfa shoot biomass for the removal of gold from aqueous solutions. The accumulation process involves the reduction of Au(III) to colloidal Au(0) and is shown to increase at elevated temperatures and at lower pH. X-ray absorption spectroscopy (XAS) was used to determine that gold(III) was reduced to form gold(0) colloids, which varied in size depending on the pH of the initial solution. The gold cluster radius was 6.2 ± 1 Å at pH 5 and 9.0 ± 1 Å at pH 2. Our findings indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…The average nanoparticle size was determined using the Borowski equation. When the binding and reduction of Au(III) ions by alfalfa biomass was investigated using a combination of fl ame atomic absorption spectroscopy ( FAAS ), XAS and electrochemical techniques [62] , the results were similar to those obtained for the bioreduction of Au(III) ions by an algal biomass. Initially, 3 mol of Cl − were released per mole of gold adsorbed onto the alfalfa biomass [62] .…”
Section: Alfalfa Biomasssupporting
confidence: 52%
See 1 more Smart Citation
“…The average nanoparticle size was determined using the Borowski equation. When the binding and reduction of Au(III) ions by alfalfa biomass was investigated using a combination of fl ame atomic absorption spectroscopy ( FAAS ), XAS and electrochemical techniques [62] , the results were similar to those obtained for the bioreduction of Au(III) ions by an algal biomass. Initially, 3 mol of Cl − were released per mole of gold adsorbed onto the alfalfa biomass [62] .…”
Section: Alfalfa Biomasssupporting
confidence: 52%
“…When the binding and reduction of Au(III) ions by alfalfa biomass was investigated using a combination of fl ame atomic absorption spectroscopy ( FAAS ), XAS and electrochemical techniques [62] , the results were similar to those obtained for the bioreduction of Au(III) ions by an algal biomass. Initially, 3 mol of Cl − were released per mole of gold adsorbed onto the alfalfa biomass [62] . However, XAS data showed that the ligand present on the alfalfa biomass responsible for the binding and possible reduction of the Au(III) ions was either an oxygen or a nitrogen moiety, this being the only ligand clearly visible in the EXAFS spectra after 5 min of binding [62] .…”
Section: Alfalfa Biomasssupporting
confidence: 52%
“…Previous studies have shown that alfalfa biomass has the capability to recover heavy metal ions, such as Cu(II), Cd(II), Zn(II), Pb(II), and Cr(III), from aqueous solutions. In addition, alfalfa biomass is also able to reduce the oxidation state of other metals such as Cr (VI) and Au(III) (Gardea-Torresdey et al, 1996;Tiemann et al, 1999;Gardea-Torresdey et al, 1997;Gardea-Torresdey et al, 2000). Alfalfa, a forage commonly found throughout the U.S., may be an efficient alternative to high-cost silver recuperation processes, and the use of a natural product would make the process more environmentally friendly.…”
Section: Journal Of Hazardous Substance Research 1-2mentioning
confidence: 99%
“…Various plant extracts have been explored for the synthesis of GNP, namely tamarind [19], Aloe vera [20], Pelargonium graveolens [21], Diopyros kaki [22], Eucalyptus camaldulensis and Pelargonium roseum [23], coriander [24], Scutellaria barbata [25], lemongrass [26], Datura metel, Carica papaya and Solanum melongena [27]. Additionally, live plants like Brassica juncea [28], Avena sativa [29], Medicago sativa [30] and Chilopsis linearis [31] have also been used for GNP synthesis.…”
Section: Introductionmentioning
confidence: 99%